2019
DOI: 10.1111/jcmm.14762
|View full text |Cite
|
Sign up to set email alerts
|

SP1‐mediated lncRNA PVT1 modulates the proliferation and apoptosis of lens epithelial cells in diabetic cataract via miR‐214‐3p/MMP2 axis

Abstract: Emerging evidence illustrates the critical roles of long non‐coding RNAs (lncRNAs) in the diabetes. However, the deepgoing regulation of lncRNA PVT1 in the diabetic cataract (DC) is still unclear. Here, present research investigates the pathologic roles and underlying mechanism by which lncRNA PVT1 regulates the DC pathogenesis. Human lens epithelial (HLE) B‐3 cells were induced by the high glucose (HG) to simulate the DC microenvironment models. Results revealed that lncRNA PVT1 expression was up‐regulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…Additionally, lncRNA PVT1 could promote the progression of multiple diseases. [28][29][30] Our current research further confirmed these results, suggesting that lncRNA PVT1 could act as a pro-inflammatory agent. In addition, our study firstly found that PVT1 played a key role in the occurrence of renal fibrosis, which supplemented the biological function of PVT1.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Additionally, lncRNA PVT1 could promote the progression of multiple diseases. [28][29][30] Our current research further confirmed these results, suggesting that lncRNA PVT1 could act as a pro-inflammatory agent. In addition, our study firstly found that PVT1 played a key role in the occurrence of renal fibrosis, which supplemented the biological function of PVT1.…”
Section: Discussionsupporting
confidence: 78%
“…39 Furthermore, PVT1 could modulate the proliferation and apoptosis of lens epithelial cells in diabetic cataract through regulation miR-214-3p/MMP2 axis. 30 Besides, it has been previously reported that miR-181a-5p could mediate the progression of renal fibrosis. 40 Our study was similar to these previous findings, further indicating that PVT1 knockdown inhibited the progression of renal fibrosis via sponging miR-181a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…The ceRNA hypothesis suggests that lncRNA competitively binds with microRNAs through microRNA response elements (MREs) and inhibits the down-regulation of mRNA translation by miRNAs [12]. Moreover, the role of lncRNA-miRNA-mRNA ceRNA regulatory networks has been revealed in different diseases, such as chronic myeloid leukemia, cardiovascular diseases, diabetic cataract, and myocardial infarction [13][14][15][16], which might impact the prognosis of the diseases. However, on the basis of high-throughput sequencing and large samples, only a few literatures have reported the role of ceRNA in PAAD.…”
Section: Introductionmentioning
confidence: 99%
“…As the latest generation of gene sequencing technology develops and bioinformatics advances, more and more non-coding RNAs (ncRNAs) are considered to be related to various human tumor diseases [33]. For example, NCK1-AS1 participates in the occurrence and development of tumors by affecting the level of related proteins.…”
Section: Discussionmentioning
confidence: 99%